12.0k views
4 votes
DIscrete Math

Show that the function f : X → Y is surjective iff there exists a function h : Y → X such that f · h = 1Y

1 Answer

2 votes

Answer:

Explanation:

As the statement is ‘‘if and only if’’ we need to prove two implications


  1. f : X \rightarrow Y is surjective implies there exists a function
    h : Y \rightarrow X such that
    f\circ h = 1_Y.
  2. If there exists a function
    h : Y \rightarrow X such that
    f\circ h = 1_Y, then
    f : X \rightarrow Y is surjective

Let us start by the first implication.

Our hypothesis is that the function
f : X \rightarrow Y is surjective. From this we know that for every
y\in Y there exist, at least, one
x\in X such that
y=f(x).

Now, define the sets
X_y = \{x\in X: y=f(x)\}. Notice that the set
X_y is the pre-image of the element
y. Also, from the fact that
f is a function we deduce that
X_(y_1)\cap X_(y_2)=\emptyset, and because
f the sets
X_y are no empty.

From each set
X_y choose only one element
x_y, and notice that
f(x_y)=y.

So, we can define the function
h:Y\rightarrow X as
h(y)=x_y. It is no difficult to conclude that
f\circ h(y) = f(x_y)=y. With this we have that
f\circ h=1_Y, and the prove is complete.

Now, let us prove the second implication.

We have that there exists a function
h:Y\rightarrow X such that
f\circ h=1_Y.

Take an element
y\in Y, then
f\circ h(y)=y. Now, write
x=h(y) and notice that
x\in X. Also, with this we have that
f(x)=y.

So, for every element
y\in Y we have found that an element
x\in X (recall that
x=h(y)) such that
y=f(x), which is equivalent to the fact that
f is surjective. Therefore, the prove is complete.

User Janae
by
5.7k points